2016
DOI: 10.1039/c5sm02111a
|View full text |Cite
|
Sign up to set email alerts
|

A supramolecular gel based on a glycosylated amino acid derivative with the properties of gel to crystal transition

Abstract: Here we report the generation of a novel gelator from a glycosylated amino acid derivative, which contained three structural units, an aromatic residue, a carbohydrate moiety and a tert-butyl group in a single molecule. These structural units can promote the supramolecular self-assembly of this gelator in both aprotic and protic solvents via coordinated π-π stacking, multiple hydrogen binding and van der Waals interactions. More importantly, due to their non-equilibrium natures, the organogels formed in DCM, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Thev iscoelastic properties of the gels were measured by oscillatory rheology experiments.G enerally,t he viscoelastic behavior of ag el is determined by two key parameters,t he storage modulus (G')a nd the loss modulus (G''), which represent the ability of agel to return to its original geometry and the tendency of amaterial to flow under applied stress. [34] Foragel, G' is greater than G'',a nd G' is very weakly dependent on the oscillatory frequency,d emonstrating the dominant elastic behavior of the gel. Ther esults shown in Figure 3a confirm the formation of an organogel and its elastic properties.Importantly,asthe cryogenic treatment was repeated for several additional cycles,t he mechanical strength increased.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thev iscoelastic properties of the gels were measured by oscillatory rheology experiments.G enerally,t he viscoelastic behavior of ag el is determined by two key parameters,t he storage modulus (G')a nd the loss modulus (G''), which represent the ability of agel to return to its original geometry and the tendency of amaterial to flow under applied stress. [34] Foragel, G' is greater than G'',a nd G' is very weakly dependent on the oscillatory frequency,d emonstrating the dominant elastic behavior of the gel. Ther esults shown in Figure 3a confirm the formation of an organogel and its elastic properties.Importantly,asthe cryogenic treatment was repeated for several additional cycles,t he mechanical strength increased.…”
mentioning
confidence: 99%
“…[26] Owing to the weakness of the non-covalent interactions exploited to maintain the aforementioned equilibrium, such metastable physical gels can be converted into thermodynamically stable crystals.The gel-crystal transitions in several systems have been observed to be triggered by various stimuli, such as light irradiation, pH changes,heating/ cooling, ac hange in ionic strength or solvent, or even storage. [27][28][29][30][31][32][33][34][35] Fori nstance,o ur group has demonstrated that the structural transition from an organogel to flower-like microcrystals can be induced in the dipeptide self-assembly system by using ethanol as ac o-solvent. [18] Herein, we explore cryogenic treatment as an approach to achieve at unable transition from ad ipeptide-based selfassembled organogel to aw ell-ordered crystal (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the weakness of the non‐covalent interactions exploited to maintain the aforementioned equilibrium, such metastable physical gels can be converted into thermodynamically stable crystals. The gel–crystal transitions in several systems have been observed to be triggered by various stimuli, such as light irradiation, pH changes, heating/cooling, a change in ionic strength or solvent, or even storage . For instance, our group has demonstrated that the structural transition from an organogel to flower‐like microcrystals can be induced in the dipeptide self‐assembly system by using ethanol as a co‐solvent …”
Section: Methodsmentioning
confidence: 99%
“…The viscoelastic properties of the gels were measured by oscillatory rheology experiments. Generally, the viscoelastic behavior of a gel is determined by two key parameters, the storage modulus ( G′ ) and the loss modulus ( G′′ ), which represent the ability of a gel to return to its original geometry and the tendency of a material to flow under applied stress . For a gel, G′ is greater than G′′ , and G′ is very weakly dependent on the oscillatory frequency, demonstrating the dominant elastic behavior of the gel.…”
Section: Methodsmentioning
confidence: 99%